Some Considerations On the ‘maestros de hacer breviarios y escrituras de molde’ Juan de Bobadilla and Álvaro de Castro (1483) - Rial Costas, Benito (Revista General de Información y Documentación, 2012)
In 1483, the Archdiocesan Council of Santiago agreed with the ‘maestros de hacer breviarios y escrituras de molde’ Juan de Bobadilla and Álvaro de Castro on printing one hundred twenty copies of a Compostelan breviary. A few years after this document’s discovery, at the end of nineteenth century, historiography created Juan de Bobadilla and Álvaro de Castro’s biographies, which are still today largely accepted. This article reviews the history of this biographic creation, exposing the weaknesses of the arguments that have been used in their ongoing reproduction. The article proposes that Juan de Bobadilla and Álvaro de Castro’s biographic data should be limited to those contained in the 1483’s agreement. It questions, however, the interpretation that historians have made of this document.